Using language games for vocabulary retention in a rural primary school in Sarawak / Lydia Zeta Donald Stavy, Frankie Subon and Norseha Unin - Donald Stavy, Lydia Zeta; Subon, Frankie; Unin, Norseha (Universiti Teknologi MARA Cawangan Sarawak, 2019)
This study seeks to examine the impact of using language games on students' vocabulary retention. Six language games were chosen for this study; (1) describe it, (2) matching pairs, (3) jigsaw puzzle, (4) board rush, (5) ball games and (6) true or false. The rationale for choosing six different games is based on the understanding that students require at least five to sixteen exposures to learn a new word (Nation's, 2001) for effective vocabulary retention. For this study, vocabulary retention is the ability to keep or retain the new words that are taught for the duration of two weeks. The Pre-test and post-test were used to measure the vocabulary retention of the students. Prior to the pre-test, all 64 participants were taught for two weeks using the conventional teaching method by getting students to look words up in the dictionary, write definitions, and use the words in sentences (Basurto, 2004).For this traditional teaching, the eight new words were chosen from unit 10 of the text book for grade three of Malaysian elementary schools. For the next stage, the students were taught eight new words from unit 11 of the same text book. After two weeks of teaching using the above six games, the students were given the posttest. The findings revealed that there was a significant difference in vocabulary retention between the pre-test and post-test. The participants were able to retain significantly more words in the post-test than in the pre-test. In fact, they achieved better results in the post-test (M=63.45) than in the pre-test (M=58.71). This study reveals that language games can help to boost the students' vocabulary retention if they are given a chance to learn and practice English language in a fun learning environment.